Development of a Modelling to Correlate Site and Diameter of Brain Metastases with Hippocampal Sparing Using Volumetric Modulated Arc Therapy. (9th October 2013) - Chiesa, Silvia; Balducci, Mario; Azario, Luigi; Gaudino, Simona; Cellini, Francesco; Mattiucci, Gian Carlo; Colosimo, Cesare; Valentini, Vincenzo
Abstract : Purpose . To correlate site and diameter of brain metastases with hippocampal sparing in patients treated by RapidArc (RA) technique on whole brain with simultaneously integrated boost (SIB). Methods and Materials . An RA plan was calculated for brain metastases of 1-2-3 cm of diameter. The whole brain dose was 32.25 Gy (15 fractions), and SIB doses to brain metastases were 63 Gy (2 and 3 cm) or 70.8 Gy (1 cm). Plans were optimized and evaluated for conformity, target coverage, prescription isodose to target volume, homogeneity index, and hippocampal sparing. Results . Fifteen brain lesions and RA plan were generated. Hippocampal volume was 4.09 cm 3, and hippocampal avoidance volume was 17.50 cm 3 . Related to site of metastases, the mean hippocampal dose was 9.68 Gy 2 for occipital lobe, 10.56 Gy 2 for frontal lobe, 10.56 Gy 2 for parietal lobe, 10.94 Gy 2 for deep brain structures, and 40.44 Gy 2 for temporal lobe. The mean hippocampal dose was 9.45 Gy 2, 10.15 Gy 2, and 11.70 Gy 2 for diameter's metastases of 1.2 and 3 cm, respectively, excluding results relative to temporal brain lesions. Conclusions . Location more than size of metastases can adversely influence the hippocampus sparing. Further investigation is necessary to meet definitive considerations.